2007
DOI: 10.1677/jme-07-0076
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic factor 1/adrenal 4 binding protein transforms human bone marrow mesenchymal cells into steroidogenic cells

Abstract: Steroidogenic factor 1/adrenal 4 binding protein (SF-1/Ad4BP) is an essential nuclear receptor for steroidogenesis as well as for adrenal and gonadal gland development. Mesenchymal bone marrow cells (BMCs) contain pluripotent progenitor cells, which differentiate into multiple lineages. In a previous study, we reported that adenovirus-mediated forced expression of SF-1 could transform mouse primary long-term cultured BMCs into steroidogenic cells. For future clinical application, trials using human BMCs would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…This method can also differentiate human BM-MSCs into cortisol-producing cells in response to adrenocorticotropic hormone stimulation, which are similar to the zona fasciculata cells of the adrenal gland. Additionally, BM-MSCs transform to steroidogenic cells by adenovirus-mediated transient expression of SF-1 Tanaka et al, 2007;Wei et al, 2012;Yanase et al, 2006). These studies are consistent with the concept that SF-1 is a master regulator for steroidogenesis.…”
Section: Differentiation Of Stem Cells Into Steroidogenic Cells By Sfsupporting
confidence: 85%
“…This method can also differentiate human BM-MSCs into cortisol-producing cells in response to adrenocorticotropic hormone stimulation, which are similar to the zona fasciculata cells of the adrenal gland. Additionally, BM-MSCs transform to steroidogenic cells by adenovirus-mediated transient expression of SF-1 Tanaka et al, 2007;Wei et al, 2012;Yanase et al, 2006). These studies are consistent with the concept that SF-1 is a master regulator for steroidogenesis.…”
Section: Differentiation Of Stem Cells Into Steroidogenic Cells By Sfsupporting
confidence: 85%
“…However, a limitation of current HRT is the difficulty in dose optimization. For this reason, some groups are now trying to develop a method to transplant ex vivo-generated steroidogenic cells to allow control of hormone concentrations in blood by the patients' own hypothalamus-anterior pituitary axis (Gondo et al 2004, Yazawa et al 2006, Tanaka et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Crawford et al (1997) using stable ectopic expression of NF5A1 in mouse embryonic stem (ES) cells, showed that NF5A1 regulates differentiation and promotes steroidogenesis in ES cells, demonstrating that NF5A1 is a dominant regulator of the steroidogenic cell phenotype. Also, it has been reported that primary long-term-cultured mesenchymal stem cells (MSCs) infected with an adenovirus-encoding bovine SF-1 (bSF-1) synthesized de novo multiple steroid hormones (Gondo et al 2004, Tanaka et al 2007). This has been confirmed by Yazawa et al (2006) who established steroidogenic cells by NF5A1 forced expression.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies attempted to produce cells resembling adrenocortical cells from human and murine cell sources. The cells of origin comprised embryonic or bone marrow-derived stem cells (including induced 'iPS' from fibroblasts), as well as mesenchymal cells derived from adipose tissue or umbilical cord R131 Review E H Gan and S H Pearce Regenerative medicine in AAD www.eje-online.org (112,113,114,115,116,117,118,119,120). Although these cell sources demonstrated their capability to be reprogrammed to steroidogenic phenotypes by the overexpression of SF1 and cAMP treatment, none fully resembled adrenocortical cells with a complete endogenous steroid profile.…”
Section: Future Therapeutic Approachesmentioning
confidence: 99%